THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT THROUGH OUTDOOR ACTIVITY AT PALOPO COKROAMINOTO UNIVERSITY - Juwita Crestiani M (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This research deals with the students’ ability in writing descriptive text through outdoor learning activity at the sixth semester of English language education study program of Palopo Cokroaminoto University. The population of this research is the sixth semester students of English language education study program in Palopo Cokroaminoto University. The total number of population was 100 students. The researcher applied the purposive sampling technique and there is 30 students as sample. Writing test is the instrument of this research. Based on the findings and discussion in the previous chapter, the researcher concludes the students’ ability in writing descriptive text through outdoor learning activity is good. It can be proven by the students’ mean score is 78 and it is categorized good.